2001
DOI: 10.1002/1521-396x(200111)188:1<389::aid-pssa389>3.0.co;2-q
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Various Pre-Treatments on Ti/Al/Ti/Au Ohmic Contacts for AlGaN/GaN HFET Devices

Abstract: The effect of a number of different treatments on the contact resistance for Ti/Al/Ti/Au (30/80/120/ 55 nm) contacts to Al 0.3 Ga 0.7 N (20 nm)/GaN HFET structures were investigated. The structures were grown by MBE. Neither preannealing of the surface at temperatures up to 1100 C in N 2 , nor etching of the surface using chemically assisted ion beam etching (CAIBE) was effective in reducing the contact resistance. Both light CAIBE etching (%5 nm) to partially remove the AlGaN layer, and deeper etching (%50 nm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…Investigations of ohmic contact formation to GaN-based semiconductors using different metallization schemes such as Ti/ Al/ Ti/ Au, Ti/ Al/ Pt/ Au, Ti/ Al/ Ni/ Au, and V / Al/ Pt/ Au have been reported. [1][2][3][4][5][6][7][8][9][10][11] In conjunction with efforts to achieve low-resistance ohmic contacts to n-GaN using low work-function metal contacts, surface treatment techniques have also been proposed as an additional route to improve ohmic contacts, as the nature of the GaN surface is crucial to the formation of high quality ohmic contacts. Gallium oxide is formed on GaN and AlGaN surfaces when epilayers are exposed to ambient atmosphere.…”
Section: Introductionmentioning
confidence: 99%
“…Investigations of ohmic contact formation to GaN-based semiconductors using different metallization schemes such as Ti/ Al/ Ti/ Au, Ti/ Al/ Pt/ Au, Ti/ Al/ Ni/ Au, and V / Al/ Pt/ Au have been reported. [1][2][3][4][5][6][7][8][9][10][11] In conjunction with efforts to achieve low-resistance ohmic contacts to n-GaN using low work-function metal contacts, surface treatment techniques have also been proposed as an additional route to improve ohmic contacts, as the nature of the GaN surface is crucial to the formation of high quality ohmic contacts. Gallium oxide is formed on GaN and AlGaN surfaces when epilayers are exposed to ambient atmosphere.…”
Section: Introductionmentioning
confidence: 99%
“…Geng et al 75 studied effects of the types of metal catalyst used in electrodeless photoelectrochemical etching, and found that the promotion order of metals to the etching rate was Ag < Au < Ir < Pt, and the difference to the band bending caused by the metal-semiconductor contact. Additionally, Bardwell et al 76,77 also used KSO system as the etchant, and carried out a series of studies on the effect of parameters on the etching morphology in the electrodeless photoelectrochemical etching of GaN.…”
Section: Electrochemical Etching Of Ganmentioning
confidence: 99%